Homologous chromosomes undergo sequential quasi-stable interactions during meiotic prophase - Newman, Trent (University of Dundee, 2021)
The pairing of homologous chromosomes in meiosis I is essential for sexual reproduction and is mediated, in part, by the formation and repair of Spo11-induced DNA double strand breaks (DSBs). In budding yeast, each cell receives 150-200 DSBs, yet only a fraction go on to form crossover products. How and why the cell initially coordinates so many interactions along each chromosome is not well understood. Using a fluorescent reporter-operator system (FROS), we measure the kinetics of interacting homologous loci at various stages of meiosis. We find that while tagged loci undergo considerable motion throughout prophase I, they are constrained in how far they can diffuse from their homolog pair. This effective tethering radius decreases over the course of meiosis in a DSB-dependent manner. We develop a theoretical model that captures the biological contributions of centromere attachment to the nuclear envelope, homolog pairing, and nuclear confinement. With this model, we demonstrate that the experimentally observed heterogeneity in single-cell behavior and the effective tethering between loci is captured for two polymers forming randomly-spaced linkages. The small number of connections required to reproduce our data demonstrates that a single linkage site between homologous chromosomes can constrain the movement of loci up to hundreds of kilobases away.
Live-cell imaging was used to measure the distance between two fluorescently-tagged chromosomal loci over time in yeast nuclei throughout prophase I of meiosis.
Keywords: FOS: Biological sciences